Visual pollution in the Algerian city: manifestations and causes. Case Study of the City of Batna - Mansour, Khemissi; Addad, Mohamed Elcharif (Technium Social Sciences Journal, 2022)
Construction is one of the most prominent phenomena in Algeria's cities. which resulted in deformation of the appearance of residential buildings that lacked aesthetic characteristics, The importance of the study of visual pollution lies in its direct relationship with the visual image of the city. The research aims to study the manifestations of visual pollution in the urban environment and to learn the factors and causes that led to it by studying the status of the centre of the city of Batna located In the Land Occupancy Scheme No. 8, based on the analytical and descriptive curriculum, the study showed the impact of Visual pollution and its relationship to the violation of building regulations.